Employing ProteoWizard to Convert Raw Mass Spectrometry Data. Issue 1 (17th June 2014) - Holman, Jerry D.; Tabb, David L.; Mallick, Parag
Abstract: After raw data have been captured by mass spectrometers in biological LC‐MS/MS experiments, they must be converted from vendor‐specific binary files to open‐format files for manipulation by most software. This protocol details the use of ProteoWizard software for this conversion, taking format features, coding options, and vendor particularities into account. This protocol will aid researchers in preparing their data for analysis by database search engines and other bioinformatics tools. Curr. Protoc. Bioinform . 46:13.24.1‐13.24.9. © 2014 by John Wiley & Sons, Inc.